ETHICS OF GADGET USE AMONG ELEMENTARY SCHOOL STUDENTS: A REVIEW FROM THE PERSPECTIVE OF MORAL PHILOSOPHY - yayang karlina; Yusuf Tri Herlambang; Dede Margo Irianto (SOSIOEDUKASI, 2026)
The increase in gadget use among elementary school students is a phenomenon that is not only pedagogical and psychological in nature, but also has complex ethical implications. This article aims to examine the use of gadgets among elementary school children through a critical synthesis of various moral philosophy perspectives within the framework of technoethics, so that technology is not understood merely as a learning tool, but as an agent that shapes children's habits, social relationships, and value orientations. This study uses the Systematic Literature Review (SLR) method based on PRISMA standards on 22 scientific articles published in the last five years and sourced from Google Scholar, ScienceDirect, and SpringerLink databases. The analysis was conducted using a thematic approach to integrate empirical findings with the perspectives of deontological ethics, utilitarianism, virtue ethics, care ethics, discourse ethics, responsibility ethics, and family ethics. The results showed that unethical gadget use has the potential to reduce empathy, weaken social interaction, disrupt cognitive function, and hinder the formation of children's moral character. From a technological ethics perspective, these findings confirm that the effectiveness of educational technology cannot be separated from the moral responsibility of adults as technology controllers. This article concludes that the use of gadgets by elementary school students should be viewed as a moral practice that requires a normative and conceptual framework, not merely technical regulations, so that technology can contribute positively to the human and moral development of children.